2020
DOI: 10.3390/microorganisms8101488
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Zophobas morio Hemolymph against Bovine Mastitis Pathogens

Abstract: Coliforms and Staphylococcus spp. infections are the leading causes of bovine mastitis. Despite extensive research and development in antibiotics, they have remained inadequately effective in treating bovine mastitis induced by multiple pathogen infection. In the present study, we showed the protective effect of Zophobas morio (Z. morio) hemolymph on bovine mammary epithelial cells against bacterial infection. Z. morio hemolymph directly kills both Gram-positive and Gram-negative bacteria through membrane perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The wound area temperature of hemolymph antibacterial protein treatment group was closer to the control group, which suggests that hemolymph can relieve symptoms of elevated local wound temperature. Z. morio hemolymph showed excellent antibacterial activity in vitro, and had a superior bactericidal effect on S. aureus ATCC25923 [17]. Our study showed that the Z. morio hemolymph can significantly reduce the load of S. haemolyticus in the wound tissue of mice, which may be related to a previous report, in which Z. morio hemolymph can increase the permeability of the bacterial membrane, destroy cell membrane integrity and kill the bacteria [17].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The wound area temperature of hemolymph antibacterial protein treatment group was closer to the control group, which suggests that hemolymph can relieve symptoms of elevated local wound temperature. Z. morio hemolymph showed excellent antibacterial activity in vitro, and had a superior bactericidal effect on S. aureus ATCC25923 [17]. Our study showed that the Z. morio hemolymph can significantly reduce the load of S. haemolyticus in the wound tissue of mice, which may be related to a previous report, in which Z. morio hemolymph can increase the permeability of the bacterial membrane, destroy cell membrane integrity and kill the bacteria [17].…”
Section: Discussionsupporting
confidence: 83%
“…In our previous study, a natural hemolymph antimicrobial extract from Z. morio had a positive antibacterial effect, which can maintain antibacterial ability after various physical and chemical treatments [17]. At the same time, it does not have hemolysis ability and obvious cytotoxicity at an effective bactericidal concentration range [17].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The spectrum of Z. morio applications is continuously growing. Recently, Du et al (2020) showed that Z. morio hemolymph can effectively protect bovine mammary epithelial cells against bacterial infections and proposed Z. morio hemolymph as an efficient, alternative therapeutic candidate for bovine mastitis, the most prevalent disease affecting the dairy industry worldwide. Additionally, this species is often used as a model organism.…”
Section: Other Applicationsmentioning
confidence: 99%